Structural racism : and how to fight it - Bipasha Sinha; Saha, Upasana (New Delhi Wordpen Academics Publications, 2025)
"Structural Racism and How to Fight It" is a comprehensive exploration of the pervasive systems and institutions that perpetuate racial inequality. This book delves into the historical roots and contemporary manifestations of structural racism, examining how policies, practices, and power dynamics contribute to disparities in areas such as housing, education, employment, healthcare, and criminal justice. Whether you're an activist, policymaker, educator, or concerned citizen, ""Structural Racism and How to Fight It"" serves as a valuable resource for understanding and dismantling the systemic barriers that perpetuate racial injustice and inequality."
Keywords: Ethnic and national groups